Given that x + y = 180, p + q = 180, and p = x. Show that y = q.
Which step would be used to prove the argument?
3 answers
To prove that y = q, we can use the substitution property.
what would the equation look like?
To prove that y = q, we can start with the given equations:
1) x + y = 180
2) p + q = 180
And we are also given that p = x, so we can substitute this value in equation 2 to get:
x + q = 180
Now, we need to show that y = q.
1) x + y = 180
2) p + q = 180
And we are also given that p = x, so we can substitute this value in equation 2 to get:
x + q = 180
Now, we need to show that y = q.